Humans identify negative (but not positive) arousal in silver fox vocalizations: implications for the adaptive value of interspecific eavesdropping - Filippi, Piera (Curr Zool, 2017)
The ability to identify emotional arousal in heterospecific vocalizations may facilitate behaviors that increase survival opportunities. Crucially, this ability may orient inter-species interactions, particularly between humans and other species. Research shows that humans identify emotional arousal in vocalizations across multiple species, such as cats, dogs, and piglets. However, no previous study has addressed humans’ ability to identify emotional arousal in silver foxes. Here, we adopted low- and high-arousal calls emitted by three strains of silver fox—Tame, Aggressive, and Unselected—in response to human approach. Tame and Aggressive foxes are genetically selected for friendly and attacking behaviors toward humans, respectively. Unselected foxes show aggressive and fearful behaviors toward humans. These three strains show similar levels of emotional arousal, but different levels of emotional valence in relation to humans. This emotional information is reflected in the acoustic features of the calls. Our data suggest that humans can identify high-arousal calls of Aggressive and Unselected foxes, but not of Tame foxes. Further analyses revealed that, although within each strain different acoustic parameters affect human accuracy in identifying high-arousal calls, spectral center of gravity, harmonic-to-noise ratio, and F0 best predict humans’ ability to discriminate high-arousal calls across all strains. Furthermore, we identified in spectral center of gravity and F0 the best predictors for humans’ absolute ratings of arousal in each call. Implications for research on the adaptive value of inter-specific eavesdropping are discussed.